Habitat requirements of Boreal Owl (Aegolius funereus) and Pygmy Owl (Glaucidium passerinum) in mountainous populations on the Balkan Peninsula :Powerpoint - Stoyanov, S.I. (University of Twente, 2020)
This lecture presents: Study area: Map of Bulgaria with georeferenced image of high resolution satellite imagery ofthe study area from Google Earth, Shiroka Laka Forest Enterprise in “Trigrad-Mursalitsa” Natura-2000 zone according to the Birds Directive; Studied species: Two species of boreal owls; Field work performed in autumn 2012, 2013 and 2014.